The Role of Wali Nanggroe Institution to Realize Peace in the Asymmetric Decentralization: the Case of Indonesia - Delfi Suganda; Retno Saraswati; Nabitatus Sa'adah (Yustisia Jurnal Hukum, 2021)
Aceh is a unique area in Indonesia based on Law Number 11 of 2006 concerning the Government of Aceh. One of its features is the establishment of the Wali Nanggroe Institution which is the highest customary institution that aims to maintain peace in Aceh and participate in the world peace process. It is unique in the Indonesian constitutional system because its officers are former combatants of the Free Aceh Movement. This study would like to examine the opportunities and role of the Wali Nanggroe Institution in realizing peace domestically and globally. There are several opportunities for the Wali Nanggroe Institution in peace efforts in a conflicted country; among others, the Wali Nanggroe Institution can carry out the function of peace at the local, national and international levels. It can apply due to the legitimacy of laws and regulations, support from local political parties that dominate Aceh's parliament, and good relations with several foreign countries, such as the "Moro" separatist group from the Philippines had studied with Wali Nanggroe how the peace process from civil war can be realized